THE IMPLEMENTATION OF PROCESS STANDARD OF TEACHING ENGLISH AT SMK NEGERI 1 GIANYAR - ., I WAYAN SUTENA; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris, 2013)
The present study only focused on the implementation of process standard in teaching English in terms of planning, teaching process, assessment used in the lesson plan and the problems faced by the teacher in implementing the process standard of teaching English in SMK Negeri 1 Gianyar. The subjects of the study were the students, and the English Teachers in SMK Negeri 1 Gianyar. There were some resources used by the researcher to help him in collecting data such as checklist, observation sheet, and interview guide. The data were described based on the planning, implementation of process standard in teaching and the assessment used in the lesson plan. Based on the findings and discussion, the researcher found some points related to the implementation of process standard in teaching English in SMK Negeri 1 Gianyar, namely: a) The English teachers at SMK Negeri 1 Gianyar still had problems in term of planning process standard in teaching English. It was found that the all subjects did not make the preparation for teaching English by themselves. They made it because of the formal supervision only. b) The English teachers at SMK Negeri 1 Gianyar did not fully apply the process standard in teaching English.c) It was found that the types of assessment used by the subjects in their lesson plan were spoken and written test. The assessment was not considered relevance because It did not cover three domains of learning. They were: cognitive domain, affective domain and psychomotor domain. In cognitive domain the teacher did not ask the students to produce sentences and answering questions based on the topic. In affective domain, the teacher did not ask the students to work in pair to make a dialog. The last in psychomotor domain, they did not ask the students to perform their work.keyword : Process standard, Lesson plan, Assessment, Language learning and language teaching